Pengaruh Quality Product, Brand Image, dan Customer Satisfaction terhadap Customer Online Purchase Intention - Griselda Nadia Novit; Rezi Erdiansyah (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
This study aims to examine the effect of product quality, brand image, and customer satisfaction on online purchase intention. The number of respondents involved in this study was 110 respondents, all respondents were customers of Abuba Steak’s customers. This research is a research with a quantitative approach. Research data was obtained from the result of filling out the questionnaire. The research data were then analyzed using multiple linear regression analysis techniques with the help of the SPSS version 25 program. Based on the results of the analysis in this study, the results showed that: (1) Product quality had a positive and significant effect on online purchase intention, the better the quality of the Abuba Steak’s product, the higher the customer interest in buying Abuba Steak’s products; (2) Brand image has a positive and significant effect on online purchase intention, the better the brand image of Abuba Steak’s products, the higher customer interest in buying Abuba Steak’s products; (3) Customer satisfaction has a positive and significant effect on online purchase intention, the higher the customer satisfaction of Abuba Steak, the higher the customer’s interest in buying Abuba Steak’s products; (4) Product quality, brand image, and customer satisfaction simultaneously affect online purchase intention with a large contribution of 67.3%. Tujuan penelitian ini menguji pengaruh kualitas produk, citra merek, dan kepuasan pelanggan terhadap niat beli online. Jumlah responden di penelitian ini adalah 110 responden, semua responden adalah pelanggan dari pelanggan Abuba Steak. Pendekatan kuantitatif digunakan dalam penelitian ini. Data penelitian didapatkan dari hasil pengisian kuesioner. Data penelitian kemudian dianalisis melalui teknik analisis regresi linier berganda dengan program SPSS versi 25. Sesuai dengan hasil analisis dalam penelitian ini diperoleh hasil: (1) Kualitas produk berpengaruh positif dan signifikan terhadap niat beli online, kualitas produk Abuba Steak yang semakin baik, sehingga minat beli pelanggan Abuba Steak juga semakin tinggi; (2) Citra merek berpengaruh positif dan signifikan terhadap niat beli online, citra merek produk Abuba Steak yang semakin baik, sehingga minat pelanggan untuk membeli produk Abuba Steak juga semakin tinggi; (3) Kepuasan pelanggan berpengaruh positif dan signifikan terhadap niat beli online, kepuasan pelanggan Abuba Steak yang semakin tinggi, minat pelanggan membeli produk Abuba Steak juga semakin tinggi; (4) Kualitas produk, citra merek, dan kepuasan pelanggan secara simultan mempengaruhi niat pembelian online dengan kontribusi yang besar sebesar 67,3%.